Serum Lactate as A Predictor of Shock Severity in Pediatric Intensive care Units - Mubara Khizer, Faiqa Taj, Uzma Suleman, Fawad Ahmed, Asma Arif (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To evaluate serum lactate as a predictor of shock severity and clinical outcomes in pediatric patients admitted to the pediatric intensive care unit. Methodology: This cross-sectional study was conducted at Paediatrics ICU Department of Mayo Hospital Lahore from January 2023 to June 2023. A total of 155 pediatric patients diagnosed with shock were enrolled using a non-probability consecutive sampling technique. Demographic characteristics, clinical parameters, and laboratory findings were recorded. Serum lactate levels were measured at admission and patients were monitored for outcomes including mechanical ventilation requirement, development of multiorgan dysfunction, duration of PICU stay, and mortality. Results: The mean age of patients was 5.8 ± 3.6 years and males constituted 58.1% of the study population. Septic shock was the most common type of shock observed in 46.5% of patients. The mean serum lactate level at admission was 4.7 ± 2.1 mmol/L. Patients with severe shock had significantly higher lactate levels (6.5 ± 2.4 mmol/L) compared with those with moderate (4.5 ± 1.8 mmol/L) and mild shock (3.1 ± 1.2 mmol/L). Mechanical ventilation was required in 37.4% of patients and was associated with higher lactate levels. Multiorgan dysfunction developed in 29.7% of patients and was also associated with significantly elevated lactate levels. Overall mortality was 13.5%, and non-survivors had markedly higher lactate levels compared with survivors. Conclusion: Serum lactate is a reliable predictor of shock severity and adverse outcomes in pediatric intensive care units. Elevated lactate levels are associated with increased disease severity, multiorgan dysfunction, and mortality, emphasizing the importance of early lactate assessment in the management of pediatric shock. Keywords: Serum lactate, pediatric shock, hyperlactatemia, critical illness, prognosis.